Anatomical Relationship of Lingual Nerve to the Region of Mandibular Third Molar - Marcelo Breno Meneses Mendes; Carla Maria de Carvalho Leite Leal Nunes; Maria Cândida de Almeida Lopes (Stilus Optimus, 2014)
Objectives: This study evaluated the relationship of the lingual nerve with the adjacent anatomical structures of the mandibular third molar region, influencing the dentist to be aware of the variability of these relationships. Material and Methods: Samples of 24 human corpse half-heads were selected and divided according with the presence or absence of the mandibular third molars. The lingual nerve (LN) was explored, showing its run from the oblique line until its crossing with the submandibular gland duct. The measurements along the LN and the adjacent anatomical structures were taken at the retromolar, molar and sublingual region with the use of a digital caliper. Results: The distance from the LN and the third molar socket, which represents the horizontal distance of the lingual plate to the nerve, on average, was 4.4 mm (SD 2.4 mm). The distance from the LN and the lingual alveolar rim, which represents the vertical relationship between the nerve and the lingual alveolar rim of the third molar socket, on average, was 16.8 mm (SD 5.7 mm). The LN has a varied topography that leaves it very vulnerable during any procedure executed in this region. Conclusions: Unless adequate protection of the lingual nerve is acquired by following an adequate surgical technique, the lingual nerve will always be vulnerable to damage during surgical intervention or manipulation in this region.